Promoting Biodiversity: Vegetation in a Model Small Park Located in the Research and Educational Centre - Jan Winkler (Polish Society of Ecological Engineering (PTIE), 2022)
University campuses, as important elements of urban greenery, are related with a positive impact on student health and well-being. Supply unique possibilities for estimating biodiversity change. This study focuses on the biodiversity in the Campus. The study aims at: assessing the plant biodiversity occurring in the park; assessing the representation of native species and determining the frequency at which invasive species occur; and recommending an adaptation of the park management. The Park was sub-divided into biotopes and a phytocoenological relevé was recorded. Park projects create biodiversity islands that may contribute to improve urban space. A species composition that is close to natural vegetation creates a space for native species, which thus better adapt to living in urban conditions. Localities created by humans, which imitate natural ecosystems, increase the biodiversity and are valuable natural islands in cities. The semi-natural phytocoenoses however, not resist the occurrence of invasive plant species. Regarding the small size of the studied park, manual elimination or cutting of invasive plant species is sufficient.